2011
DOI: 10.1097/bot.0b013e3181d8290e
|View full text |Cite
|
Sign up to set email alerts
|

Operative versus Nonoperative Management of Displaced Midshaft Clavicle Fractures: A Prospective Cohort Study

Abstract: In this prospective cohort study, primary open reduction and internal plate fixation of acute displaced midshaft clavicular fractures resulted in improved outcomes and a decreased rate of nonunion and symptomatic malunion compared with nonoperative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
90
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(97 citation statements)
references
References 23 publications
3
90
0
2
Order By: Relevance
“…Collation of literature on clavicle fractures suggests that the expected nonunion rate is 8.6%. This percentage was derived from the reported healing rate in 12 separate publications [59][60][61][62][63][64][65][66][67][68][69][70] spanning the period from 2004 to 2013 and including 3168 patients treated with a range of conservative and operative methods. Both samples are large, and the nonunion rate in our database again differs by less than a percentage point from the literature values.…”
Section: Discussionmentioning
confidence: 99%
“…Collation of literature on clavicle fractures suggests that the expected nonunion rate is 8.6%. This percentage was derived from the reported healing rate in 12 separate publications [59][60][61][62][63][64][65][66][67][68][69][70] spanning the period from 2004 to 2013 and including 3168 patients treated with a range of conservative and operative methods. Both samples are large, and the nonunion rate in our database again differs by less than a percentage point from the literature values.…”
Section: Discussionmentioning
confidence: 99%
“…Three patients had delayed union which were united by 16-18 weeks (5%) and one case of failure of osteosynthesis developed non-union (1.7%). The studies by the COTS [13] and Kulshrestha et al [14] reported non-union rate of 3% and 0% respectively. A major complication in our study was one case of implant failure in out of 60 patients (1.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Patient is satisfied with the outcome as he has full ROM and strength and no pain except a small prominence of the implant. Reported rate of failure of osteosynthesis in literature is about 0-16% [1,10,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…7) Displaced fracture of the clavicular midshaft shows a higher rate of delayed and nonunion than nondisplaced fracture patterns. [8][9][10][11][12][13][14] However, with the development of plates such as low-profile LCP, more stable fixation is possible and good results have been reported after surgical treatment in clavicle midshaft fracture. 4,5) 15) suggested leaving a plate in place for 12 to 18 months and placement of restrictions against contact sports for 2 to 3 months after plate removal.…”
Section: Discussionmentioning
confidence: 99%